Main Harbour, Port of Spain, Trinidad. - (:unkn) unknown (Syncreators Ltd., 2009)
A picture of the Port-of-Spain Harbour circa the 1970s. You can see boats docked. Also seen is a Trinidad and Tobago flag attached to one of the boats. Postcard number 6901AB.
Colour: Coloured; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Habors--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Flags--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain